Quality of rice bran-containing hotdogs after pasteurization and subsequent freeze-thaw cycles - Marte, Kristia May
ABSTRACT The study was conducted to establish the freeze-thaw quality of premium and low cost hotdogs incorporated with SRB subjected to pasteurization and 5 sequential freeze-thaw cycle (12h at -5°C freezing; 12 h at 5°C thawing) in comparison to those with ISP. Physico-chemical, sensory and microbiological properties of premium and low cost hotdogs were assessed after the 0, 1, 3 and 5 freeze-thaw cycles. Except for peroxide value, the pH, penetration and moisture content values were higher for premium products relative to low cost hotdogs for formulations containing both test ingredients. Significant difference was found for penetration and peroxide values as well as color parameters of formulations with ISP and those with SRB (P<0.05). Sensory evaluation results showed significant difference for the acceptability of texture, snap and moistness of processed premium and low cost hotdogs for both test formulations (P<0.05). There was also a significant difference for the acceptability of texture, mouth feel, flavor and juiciness of fried premium and low cost hotdogs for formulations with both test ingredients (P<0.05). Initial intensity ratings did not significantly differ with intensity ratings as the freeze-thaw cycle increased (P<0.05) which indicated that the freeze-thaw cycle did not significantly affect the overall appearance and palatability characteristics of the hotdogs. Microbiological results showed that initial TCC was found to be > 3 but < 4 log cfu/g. The YMC obtained was less than the sensitivity of the technique (<10 cfu/g). Premium and low cost hotdogs incorporated with SRB were found to be comparable in shelf-life stability, overall appearance and palatability characteristics with premium and low cost formulations incorporated with ISP subjected to the same freeze-thaw conditions. This study recommended the utilization of SRB in the production of premium and low cost hotdogs expected to be exposed to thermal abuse conditions in the cold chain.